Effect of combination of organosulfur and polyphenols organic fungicide on Ganoderma-infected oil palm seedlings - Yusup, Ciptadi Achmad; Eris, Deden Dewantara; Mulyatni, Agustin Sri; Pradana, Mahardika Gama; Widiastuti, Happy; Santoso, Djoko (Universitas Lampung, 2026)
The curative potential of an organic fungicide against Ganoderma boninense was previously assessed in vitro and yielded promising results. This organic fungicide was formulated using a combination of organosulfur compounds and polyphenols (OSC-P) as active ingredients. This study aimed to evaluate the effectiveness of OSC-P application in controlling basal stem rot (BSR) disease in infected oil palm seedlings of different varieties and to determine the optimum application dose. Two oil palm varieties were used: a G. boninense-susceptible variety and a moderately tolerant variety. The seedlings were artificially infected with G. boninense using inoculated rubber wood blocks (RWB). OSC-P was applied to 16-week-old seedlings by soil drenching at a volume of 200 mL per plant at 2-week intervals for 24 weeks. A total of six treatments, including controls, were arranged with four replications and observed at 4-week intervals. Each replication consisted of 10 seedlings. Observed parameters included disease incidence, disease severity, and vegetative growth parameters. The results showed that OSC-P application significantly reduced the incidence and severity of BSR disease in infected oil palm seedlings. BSR symptoms were less severe in the moderately tolerant variety than in the susceptible variety; however, disease incidence did not differ significantly between the two varieties. The optimum application dose of OSC-P was 0.8% (v/v), and variations in application dose did not significantly affect disease incidence or severity at 24 weeks after application. These findings are expected to complement existing preventive strategies for BSR management.